Mastering Autodesk Inventor 2012 and Autodesk Inventor LT 2012 - Waguespack, Curtis, 1974- (Autodesk official training guide., 2011)
"Expert author Curtis Waguespack developed this detailed reference and tutorial with straightforward explanations, real-world examples, and practical tutorials that focus squarely on teaching Inventor tips, tricks, and techniques. The author's extensive experience across industries and their Inventor expertise allows him to teach the software in the context of real-world workflows and work environments. He presents topics that are poorly documented elsewhere, such as design tactics for large assemblies, effective model design for different industries, strategies for effective data and asset sharing across teams, using 2D and 3D data from other CAD systems, and improving designs by incorporating engineering principles.Mastering Inventor 2011 begins with an overview of Inventor design concepts and application before exploring all aspects of part design, including sketching, basic and advanced modeling techniques, working with sheet metal, and part editing. The book then looks at assemblies and subassemblies, explaining real-world workflows and offering extensive detail on working with large assemblies.Weldment design is detailed next before the reader is introduced to the functional design using Design Accelerators and Design Calculators. The detailed documentation chapter then covers everything from presentation files to simple animations to documentation for exploded views, sheet metal flat patterns, and more. The following chapters explore crucial productivity-boosting tools, data exchange, the Frame Generator, and the Inventor Studio visualization tools. Finally, the book explores Inventor Professional's dynamic simulation and stress analysis features as well as the routed systems features (piping, tubing, cabling, and harnesses).Mastering Inventor's detailed discussions are reinforced with step-by-step tutorials, and readers can compare their work to the downloadable before-and-after tutorial files. It also features content to help readers pass the Inventor Certified Associate and Certified Professional exams and will feature instructor support materials appropriate for use in both the training and higher education channels. Mastering Inventor is the ultimate resource for those who want to quickly become proficient with Autodesk's 3D manufacturing software and prepare for the Inventor certification exams"--